Penerapan Nilai-Nilai Wata’a Wanuu ‘Alal Birri Wattaqwa Di Desa Sidodadi Bah Birong Ulu Manriah - Maysa Az-Zahra; Laila Syabrina; Fahrurrozi Fahrurrozi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out what causes or values ​​are applied in Sidodadi village, Bah Birong Ulu Manriah in terms of goodness such as Ta'awun or mutual help, as well as to make a reference in increasing awareness and acts of helping. This research uses a qualitative descriptive approach, with data sources obtained through observation, interviews and documentation. The results of the research show that the feeling of mutual assistance in Sidodadi Village, Bah Birong Ulu Manriah is still very strong and strong and is even increasing. There are several values ​​applied in the village, including religious values, social values ​​and economic values. As a student, you should take part in social activities or join an organization because it is an effective way to foster a sense of caring for others.